The Transient Receptor Potential Vanilloid 1 Is Associated with Active Inflammation in Ulcerative Colitis - Toledo-Mauriño, Joel Jesús; Furuzawa-Carballeda, Janette; Villeda-Ramírez, Marco A.; Fonseca-Camarillo, Gabriela; Meza-Guillen, Daniela; Barreto-Zúñiga, Rafael; Yamamoto-Furusho, Jesús K. (Mediators of Inflammation, 2018)
The transient receptor potential vanilloid 1 (TRPV1) may play a role in the pathogenesis of ulcerative colitis (UC). The aim of the study was to determine the gene and protein expression of TRPV1 in UC patients and noninflamed controls. Gene expression was performed by RT-PCR, and protein expression was performed by immunohistochemistry. The gene expression of TRPV1 was significantly increased in the remission UC group compared to active UC patients (P=0.002), and an upregulation of the TRPV1 gene was associated with clinical outcomes such as age at diagnosis (<40 years) (P=0.02) and clinical disease course characterized by relapsing and continuous activity (P=0.07). TRPV1 immunoreactive cells were conspicuously higher in all intestinal layers from active UC patients compared with noninflamed control tissue. These findings suggest that TRPV1 might be involved in UC pathogenesis.